Research on China Pakistan Cultural Exchange in Applied Undergraduate College under the Context of the Belt and Road Initiative - Jang Xue; Tang, Jun; Wang, Ting; Xing, Xuanyu (Pacific International Journal, 2024)
With the construction of the China-Pakistan Economic Corridor and "One Belt, One Road" Initiative(BRI), China and Pakistan maintain close cooperation in politics, economy, and other aspects, but cultural exchanges and cooperation lags behind, and has become a short board in the comprehensive relationship between China and Pakistan. To promote the friendly development of China-Pakistan relations, education is a key component of culture and the educational cooperation is vital to enhance Sino-Pakistan bilateral ties. Pakistan Study Center in Inner Mongolia Honder College of Arts and Sciences strives to play a better role in building a bridge of China-Pakistan friendship by promoting the cultural exchange. This paper mainly explores what this Pakistan Study Center have done recently in cultural exchange, to be specific, the exploration of Pakistan students’ Chinese language education in a University of the Punjab combined with the research related to Pakistani cultural learning of Chinese college students in Inner Mongolia Honder College of Arts and Sciences.